Changes in the Growth and Development of Adolescents in a Country in Socio-Economic Transition 1993-2013 - Robič Pikel Tatjana; Malus Tina; Starc Gregor; Golja Petra (Sciendo, 2020)
Changes in human growth and development depend on genetic and environmental factors. In the case of Slovenia, the environmental factors changed as a result of the period of socio-economic transition that the country underwent between 1991 and 2013. The authors used anthropometric techniques to evaluate differences in body height, proportions and sexual maturity in 1,221 adolescents aged 14 in 1993, 2003 and 2013.